Analyzing risk perception, risk attitude, and management strategy using Partial Least Squares Structural Equation Modeling (PLS-SEM) in pistachio production: the case of Siirt Province, Türkiye - Zekiye Şengül (Humanities & Social Sciences Communications)
Abstract The cultivation of pistachio (Pistacia vera L.) is a centuries-old agricultural activity that has become an important economic pursuit in different parts of the world, especially in countries like the USA, Türkiye, and Iran. This research aims to identify the determinants of risk attitude, risk perception, and risk management strategy of pistachio producers and analyze the relationship between these determinants and demographic characteristics in Siirt Province as one of the most important pistachio-producing regions in Türkiye. A total of 116 pistachio producers were interviewed face-to-face in 2023. Data were analyzed using Factor Analysis (FA) and Partial Least Squares Structural Equation Modeling (PLS-SEM). Study results contributed to the understanding of the various determinants and their interrelationships in shaping the risk management strategy of farmers. The FA results showed that pistachio producers operate in a risk environment influenced by several factors, including operational, environmental, political, economic, and financial risks. To manage these risks and consolidate their position, pistachio producers need to develop strategies that prioritize quality management, production efficiency, adaptability, income diversification, market expansion, and rational financial planning. The results of the PLS-SEM analysis revealed that water resource constraints play a critical role in shaping risk management strategies among pistachio producers. However, with increasing age and education levels, producers tend to be more risk-averse, with older and more educated producers preferring a more cautious approach to risk management. These results point to a need for joint research between producers, policymakers, and researchers to develop drought-tolerant pistachio varieties, improve irrigation techniques, prioritize water-saving technologies, and reduce environmental risks. Training programs and information dissemination strategies tailored to the different risk profiles of producers would be useful.